Antibody Secreting Cell Responses following Vaccination with Bivalent Oral Cholera Vaccine among Haitian Adults. - Wilfredo R Matias; Brie Falkard; Richelle C Charles; Leslie M Mayo-Smith; Jessica E Teng; Peng Xu; Pavol Kováč; Edward T Ryan; Firdausi Qadri; Molly F Franke; Louise C Ivers; Jason B Harris (Public Library of Science (PLoS), 2016)
BACKGROUND:The bivalent whole-cell (BivWC) oral cholera vaccine (Shanchol) is effective in preventing cholera. However, evaluations of immune responses following vaccination with BivWC have been limited. To determine whether BivWC induces significant mucosal immune responses, we measured V. cholerae O1 antigen-specific antibody secreting cell (ASC) responses following vaccination. METHODOLOGY/PRINCIPAL FINDINGS:We enrolled 24 Haitian adults in this study, and administered doses of oral BivWC vaccine 14 days apart (day 0 and day 14). We drew blood at baseline, and 7 days following each vaccine dose (day 7 and 21). Peripheral blood mononuclear cells (PBMCs) were isolated, and ASCs were enumerated using an ELISPOT assay. Significant increases in Ogawa (6.9 cells per million PBMCs) and Inaba (9.5 cells per million PBMCs) OSP-specific IgA ASCs were detected 7 days following the first dose (P < 0.001), but not the second dose. The magnitude of V. cholerae-specific ASC responses did not appear to be associated with recent exposure to cholera. ASC responses measured against the whole lipolysaccharide (LPS) antigen and the OSP moiety of LPS were equivalent, suggesting that all or nearly all of the LPS response targets the OSP moiety. CONCLUSIONS/SIGNIFICANCE:Immunization with the BivWC oral cholera vaccine induced ASC responses among a cohort of healthy adults in Haiti after a single dose. The second dose of vaccine resulted in minimal ASC responses over baseline, suggesting that the current dosing schedule may not be optimal for boosting mucosal immune responses to V. cholerae antigens for adults in a cholera-endemic area.